Appropriate Technology: Concept Evolution and Development Direction - Muhammad Yasar; Jurry Foo; Nor Diana Mohd. Idris (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2025)
Appropriate Technology (APT) is a technological approach that has developed rapidly since the mid-20th century, particularly in the context of community and economic development in developing countries. This article reviews the evolution of the APT concept, its theoretical foundations, its role in sustainable development, challenges and criticisms, and the direction of research and practice in the modern era. The literature review shows that APT has evolved from a simple technological concept tailored to community needs to a strategic framework that integrates socio-cultural, economic, and environmental aspects within the context of sustainable development and social technological innovation. This article concludes that the future direction of APT development requires strengthening integration with the global sustainability agenda and formulating comprehensive assessment indicators.